Molecular biomarkers of progression from Barrett’s esophagus to esophageal adenocarcinoma - Taylor, Luke; Alastal, Hani Naeem; Rasheed, Ashraf (Frontiers in Gastroenterology, 2023)
Introduction Barrett’s esophagus (BO) is a pre-malignant condition for esophageal adenocarcinoma (OAC), the incidence rate of which has risen dramatically over the last four decades in the Western world. The 5-year survival rate of OAC is poor, and one of the ways to improve it would be by focusing on identifying high-risk Barrett’s patients through a surveillance program. Currently, histologic dysplasia is the only recognized marker of progression to OAC. Molecular biomarkers found in tissue samples that predict which patients have a higher risk of progression to OAC may act as a reliable tool for the stratification of patients with BO. Aim To determine whether molecular biomarkers have a potential use in predicting which patients with BO have a higher risk of progression to OAC. Methods Immunohistochemistry was performed on 25 tissue samples obtained from the endoscopic biopsies of 19 patients with confirmed BO. Hematoxylin and eosin (H&E) staining was used to confirm the presence of BO and dysplasia. Staining was performed in an external independent laboratory. Statistical analysis using the Mann–Whitney U test was performed using R Studio® statistical software. Results Of the 19 patients sampled, three had low-grade dysplasia (LGD), and all had confirmed metaplasia diagnostic of BO. Expression of cyclin D1 was noted to be elevated in patients with LGD compared with those with metaplasia only (p = 0.042). Expression of Sox2 was elevated in metaplastic BO cells compared with normal squamous cells within the same stain (p = 0.046). Of all eight biomarkers tested, β-catenin had the greatest overall expression (p < 0.004). Conclusions Isolating elevated cyclin D1 in patients with LGD highlights its potential use as a biomarker in identifying BO patients at risk of developing dysplasia, and, in turn, their possible progression to OAC. Elevated levels of both Sox2 and β-catenin may also serve as markers for disease progression when overexpressed in BO patients. Both conclusions, however, would need long-term follow-up to fully establish their prognostic usefulness, as at the time of writing no patients in this study had gone on to develop OAC. Although only a small sample size was present for this study, and follow-up was limited, it serves as a strong pilot for further research into the use of novel biomarkers in predicting which BO patients are at high risk of developing dysplasia and progressing to OAC.